Grandparents Raising Grandchildren: Navigating the System Part 1 - Community Resources - Maisie Ross; Millie Ferrer; Angela Falcone (EDIS)
This document is FCS 2188-Eng, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: January 2002. Its goal is to provide grandparents with information and skills necessary to use various community resources.